Integrating psychological resilience into community health strategies: addressing stigma-induced social alienation in postoperative colorectal cancer patients - Guo, Xin; Wang, Yuqin; Han, Qi; Zhang, Rui; Liu, Shuyu; Huang, Yuenan; Zhang, Yan; Guo, Botang (Frontiers in Public Health, 2025)
BackgroundColorectal cancer (CRC) is a leading cause of mortality globally. While survival rates have improved, postoperative patients face psychosocial challenges such as social alienation and stigma, which affect their recovery. Psychological resilience may serve as a protective factor, but its role in mediating the effects of stigma on social alienation in CRC patients is not well understood.ObjectiveThis study aims to examine the mediating role of psychological resilience in the relationship between perceived stigma and social alienation among postoperative colorectal cancer patients.MethodA cross-sectional study was conducted with 382 postoperative CRC patients from three tertiary hospitals in Harbin and Shenzhen, China, between January 2023 and December 2024. Participants completed self-report measures of perceived stigma, psychological resilience, and social alienation. Data were analyzed using hierarchical regression and bootstrapping to test the mediation model.ResultPerceived stigma was positively correlated with social alienation and negatively with psychological resilience. Psychological resilience partially mediated the relationship between stigma and social alienation, explaining 30.8% of the total effect. Significant differences in social alienation were found based on gender, age, and stoma status.ConclusionPsychological resilience plays a crucial role in reducing social alienation in postoperative CRC patients. Interventions focused on enhancing resilience could help mitigate stigma and improve social reintegration. Community-based resilience programs are recommended for supporting CRC survivors.